Methadone use in pregnancy : prevalence and pregnancy outcomes in an Irish obstetric cohort - Cleary, Brian James (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Obstetrics and Gynaecology, 2011)
This thesis aimed to address current knowledge deficits relating to the issues of medication use in early pregnancy in an Irish healthcare setting and adverse perinatal outcomes in opioid-dependent pregnant women on methadone maintenance treatment.
Keywords: Obstetrics and Gynaecology, Ph.D.; Ph.D. Trinity College Dublin